Biased Distribution of Inverted and Direct Alus in the Human Genome: Implications for Insertion, Exclusion, and Genome Stability - Stenger, Judith E.; Lobachev, Kirill S.; Gordenin, Dmitry; Darden, Thomas A.; Jurka, Jerzy; Resnick, Michael A. (Genome Research, 2001)
Alu sequences, the most abundant class of large dispersed DNA repeats in human chromosomes, contribute to human genome dynamics. Recently we reported that long inverted repeats, including humanAlus, can be strong initiators of genetic change in yeast. We proposed that the potential for interactions between adjacent, closely related Alus would influence their stability and this would be reflected in their distribution. We have undertaken an extensive computational analysis of all Alus (the database is athttp://dir.niehs.nih.gov/ALU) to better understand their distribution and circumstances under which Alu sequences might affect genome stability. Alus separated by <650 bp were categorized according to orientation, length of regions sharing high sequence identity, distance between highly identical regions, and extent of sequence identity. Nearly 50% of all Alu pairs have long alignable regions (>275 bp), corresponding to nearly full-length Alus, regardless of orientation. There are dramatic differences in the distributions and character of Alupairs with closely spaced, nearly identical regions. For Alupairs that are directly repetitive, ∼30% have highly identical regions separated by <20 bp, but only when the alignments correspond to near full-size or half-size Alus. The opposite is found for the distribution of inverted repeats: Alu pairs with aligned regions separated by <20 bp are rare. Furthermore, closely spaced direct and inverted Alus differ in their truncation patterns, suggesting differences in the mechanisms of insertion. At larger distances, the direct and inverted Alu pairs have similar distributions. We propose that sequence identity, orientation, and distance are important factors determining insertion of adjacentAlus, the frequency and spectrum of Alu-associated changes in the genome, and the contribution of Alu pairs to genome instability. Based on results in model systems and the present analysis, closely spaced inverted Alu pairs with long regions of alignment are likely at-risk motifs (ARMs) for genome instability.
10.1101/gr.158801